Outbreak response operations during the US measles epidemic, 2017-19 - Elena K. Martin; Matthew P. Shearer; Marc Trotochaud; Jennifer B. Nuzzo (BMC, 2021)
Abstract Background To understand operational challenges involved with responding to US measles outbreaks in 2017-19 and identify applicable lessons in order to inform preparedness and response operations for future outbreaks, particularly with respect to specific operational barriers and recommendations for outbreak responses among insular communities. Methods From August 2019 to January 2020, we conducted 11 telephone interviews with 18 participants representing state and local health departments and community health centers that responded to US measles outbreaks in 2017-19, with a focus on outbreaks among insular communities. We conducted qualitative, thematic coding to identify and characterize key operational challenges and lessons identified by the interviewees. Results We categorized principal insights into 5 topic areas: scale of the response, vaccination operations, exclusion policies, community engagement, and countering anti-vaccine efforts. These topics address resource-intensive aspects of these outbreak responses, including personnel demands; guidance needed to support response operations and reduce transmission, such as excluding exposed or at-risk individuals from public spaces; operational challenges and barriers to vaccination and other response activities; and effectively engaging and educating affected populations, particularly with respect to insular and vulnerable communities. Conclusions Measles outbreak responses are resource intensive, which can quickly overwhelm existing public health capacities. Early and effective coordination with trusted leaders and organizations in affected communities, including to provide vaccination capacity and facilitate community engagement, can promote efficient response operations. The firsthand experiences of public health and healthcare personnel who responded to measles outbreaks, including among insular communities, provide evidence-based operational lessons that can inform future preparedness and response operations for outbreaks of highly transmissible diseases.